(untitled) (Journal of Face Aesthetics, 2019)
Introduction. Treatments in the field of aesthetic face medicine are becoming more and more popular, although awareness of the needs of their use is still very low. Aim. Presenting knowledge about facial aesthetics and estimating the needs for their application among students of dentistry at the Medical University in Poznań. Material and Methods. 60 surveys (46 women and 14 men) were included in the statistical analysis addressed to Polish- and English‑speaking students of the 3rd, 4th and 5th year of Medical and Dental studies at the Medical University of Poznań in 2019. Results. Most respondents (88%) believe that facial aesthetic medicine should be performed and it is worth starting their use at the age of 25–30 (the most common answer — 28%). 10% of the respondents used facial aesthetic medicine, and 38% facial cosmetology. Discussion. Studies by other authors indicate that the largest group of clients are women between 20–30 years old with a stable financial situation, which corresponds to the results of the survey. However, this differs from the results of the PTMEiAA research from 2017, which prove that aesthetic medicine clinics are most often visited by people aged 41 to 50 years. Customers are more willing to opt for minimally invasive procedures, which was also confirmed by the tests. Conclusions. The demand for facial aesthetics among medical students of the Medical University in Poznań, regardless of the respondents’ country of origin, is relatively low.